Desiccation cracks and their patterns : formation and modelling in science and nature /: formation and modelling in science and nature. ([2015]) - Goehring, Lucas; (Associate professor of physics), Nakahara, Akio; Dutta, Tapati; Kitsunezaki, So; Tarafdar, Sujata
No abstract available